2021
DOI: 10.21776/ub.habitat.2021.032.3.18
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness and Determining Factors of Indonesian Tea Export Volume in the World Market

Abstract: Indonesia is one of the world's tea exporters, but the decline in the volume and value of its exports to date continues to occur. This study aims to 1) analyze the production trend and export volume of Indonesian tea. 2) analyze Indonesian tea competitiveness in the International market compared to other exporter countries (China, India, Kenya, Sri Lanka, and Vietnam). 3) analyze the determining factors of Indonesia's tea export volume to 7 major destination countries (Malaysia, Russia, Pakistan, USA, Germany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Those commodities that have positive TSR value shows in Table 1. Nursodik et al (2021) supported this study result mentioned that tea, as one of the non-oil and gas commodities, had a strong comparative competitiveness and tend to be the exporter country to the international market on the stage of expanding export. Furthermore, previous research has revealed that coal commodities http://journal.uinjkt.ac.id/index.php/signifikan https://doi.org/10.15408/sjie.v11i2.24678 (Khairina & Syahputra, 2021) and furniture commodities (Elysi et al, 2018) also have strong comparative competitiveness in the international market.…”
Section: Lilis Yuliantisupporting
confidence: 79%
See 2 more Smart Citations
“…Those commodities that have positive TSR value shows in Table 1. Nursodik et al (2021) supported this study result mentioned that tea, as one of the non-oil and gas commodities, had a strong comparative competitiveness and tend to be the exporter country to the international market on the stage of expanding export. Furthermore, previous research has revealed that coal commodities http://journal.uinjkt.ac.id/index.php/signifikan https://doi.org/10.15408/sjie.v11i2.24678 (Khairina & Syahputra, 2021) and furniture commodities (Elysi et al, 2018) also have strong comparative competitiveness in the international market.…”
Section: Lilis Yuliantisupporting
confidence: 79%
“…The TSR method was initially used by Kaneko & Yanagi (1988) to calculate the competitiveness of commodity X with the product life cycle, which later concluded the competitiveness of a commodity in the global market. Trade Specialization Ratio (TSR) is an analysis tool for comparative competitiveness which shows if a country acts more as an exporter or importer (Nursodik et al, 2021). If the TSR value is positive, the country tends to act as an exporter, and the commodity has strong competitiveness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative Advantage (RCA) (Majkovic et al, 2006;Nursodik et al, 2021). This was due to the fact that the 4 main cinnamon exporting countries in the world market had a market share of 82.7%.…”
Section: Methodsmentioning
confidence: 99%
“…The nampu leaf processing business is very prospective from cost and benefit analysis as long as the raw material from nature is abundant and the export market are stable. As mentioned by (Nursodik et al, 2021) that the production factor is of the factors that affect export volume. The time required to return investment capital is relatively short because it is less than two years.…”
Section: Figure 2 Nampu Leaf Processingmentioning
confidence: 99%